Potential issues specific to cytotoxicity tests of cellulose nanofibrils. Issue 1 (18th September 2022) - Moriyama, Akihiro; Ogura, Isamu; Fujita, Katsuhide
Abstract: Cellulose nanofibrils (also called cellulose nanofibers or nanofibrillated cellulose [CNFs]) are novel polymers derived from biomass with excellent physicochemical properties and various potential applications. However, the introduction of such new materials into the market requires thorough safety studies to be conducted. Recently, toxicity testing using cultured cells has attracted attention as a safety assessment that does not rely on experimental animals. This article reviews recent information regarding the cytotoxicity testing of CNFs and highlights the issues relevant to evaluating tests. In the literature, we found that a variety of cell lines and CNF exposure concentrations was evaluated. Furthermore, the results of cytotoxicity results tests differed and were not necessarily consistent. Numerous reports that we examined had not evaluated endotoxin/microbial contamination or the interaction of CNFs with the culture medium used in the tests. The following potential specific issues involved in CNF in vitro testing, were discussed: (1) endotoxin contamination, (2) microbial contamination, (3) adsorption of culture medium components to CNFs, and (4) changes in aggregation/agglomeration and dispersion states of CNFs resulting from culture medium components. In this review, the available measurement methods and solutions for these issues are also discussed. Addressing these points will lead to a better understanding of the cellular effects of CNFs and the development of safer CNFs. Abstract : This article reviews recent information regarding the cytotoxicity testing of cellulose nanofibrils (CNFs) and highlights the issues relevant to evaluating the tests. Based on the properties of CNFs, the following points were considered: (1) endotoxin contamination, (2) microbial contamination, (3) adsorption of culture medium components to CNFs, and (4) changes in aggregation/agglomeration and dispersion states of CNFs resulting from culture medium components. In this review, the available measurement methods and solutions for these issues will be discussed.